Informed consent in an endodontic practice (LLC "Endo Press", 2020)
The article is devoted to informed consent in an endodontic practice: the legal effect of a patient act of consent to treat them and as a document between doctor and patient. The author considers the content of informed consent as a way to protect clinic and doctor in a legal relations with patient.